(untitled) (Development Service Industry Management, 2025)
The article explores in detail the conceptual and methodological foundations of understanding the economic security of an enterprise, emphasizing its dual and multifaceted nature. Economic security is analyzed not only as a protective mechanism against destabilizing internal and external threats but also as a proactive driver of long-term stability, resilience, and sustainable growth of economic systems. In this sense, economic security acquires the role of both a safeguard and a strategic resource that ensures the enterprise’s ability to adapt, innovate, and remain competitive in conditions of uncertainty and global transformation. The study presents a systematic review of different theoretical and applied approaches to the interpretation of economic security, highlighting its status as both an economic category and a broader interdisciplinary phenomenon. This dual perspective justifies the use of a conventionalist methodology, allowing for the integration and harmonization of diverse conceptual frameworks. Special attention is paid to the dichotomy of “security–development” and “security–stability,” which illustrates the complexity of balancing protective measures with growth-oriented strategies. The article also considers synthetic and convergent approaches that enable the combination of different theoretical positions into a coherent system of views. Within the paradigm of limited conventionalism, the possibility of simultaneous application of competing approaches is explored, creating a flexible epistemological platform for advancing knowledge on the subject. The analysis further relies on the conventionalist concepts developed by T. Kuhn and I. Lakatos, which provide a philosophical foundation for interpreting economic security not as a static condition but as a dynamic process of conceptual evolution. The findings suggest that each approach—whether focused on protection, resilience, adaptability, or development—contributes to the formation of a comprehensive vision of economic security. Such a vision allows for the development of practical tools and methods for its assessment, monitoring, and enhancement, ensuring that enterprises are capable of responding effectively to challenges while simultaneously building capacity for sustainable advancement. Ultimately, the article demonstrates that economic security should be understood as a systemic and integrative phenomenon that unites diverse schools of thought and creates a robust foundation for both theoretical progress and managerial practice.